Gut microbiota and its metabolites promote painful diabetic peripheral neuropathy complicated with cognitive dysfunction in mice - Yang, Junpeng; Lv, Xin; Xu, Ya; Huang, Fenglian; Yang, Xueli; Shi, Xiaoyang; Zhao, Lingyun; Liang, Chenghong; Wang, Danyu; Fang, Yuanyuan; Tang, Shasha; Liu, Yalei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPainful diabetic peripheral neuropathy (PDPN) is closely linked to cognitive dysfunction. The gut microbiota plays a pivotal role in the pathophysiology of diabetic neuropathy, but its contribution, along with related metabolites, to PDPN complicated by cognitive impairment remains poorly understood. This study aimed to explore the characteristics of gut microbiota and metabolites in db/db mice with PDPN and concomitant cognitive impairment, and to investigate the underlying mechanisms.MethodsMale homozygous db/db mice and their littermate db/m mice used as the research subjects. Thermal hyperalgesia and mechanical allodynia tests were applied to assess pain phenotypes, while the Morris water maze test was used to evaluate cognitive function. Immunohistochemistry was employed to measure intraepidermal nerve fiber density and nerve fiber markers, and Western blot analysis was used to detect pro-inflammatory cytokine levels. 16S rRNA gene sequencing of the V3-V4 regions was applied to analyze the gut microbiota structure, and LC-MS was used to analyze fecal metabolites.ResultsAt 12 weeks of age, db/db mice exhibited PDPN and cognitive deficits. The gut microbiota composition differed between the two groups, with LEfSe analysis identifying 38 key amplicon sequence variants (ASVs) enriched in db/db mice and 39 ASVs more abundant in db/m mice. Meanwhile, 398 metabolites that were significantly different between the two groups. Bidirectional mediation models indicated that Dl-lactate positively mediated the relationship between specific microbiota (Muribaculaceae (ASV243) and Ruminococcus (ASV149)) and thermal latency. In contrast, polygalic acid negatively mediated the relationship between Muribaculaceae and escape latency, as well as between Ruminococcus and thermal latency. These microbiota and metabolite changes were associated with elevated proinflammatory cytokine levels in the dorsal root ganglion (DRG) and hippocampus, respectively.DiscussionThis study highlights the intricate relationship between gut microbiota, metabolites, and both PDPN and cognitive dysfunction in db/db mice. It also provides insights into potential mechanisms underlying the pathophysiology of these comorbidities, suggesting that modulation of the gut microbiota and its metabolites may offer new therapeutic strategies.